2020
DOI: 10.1093/gerona/glaa181
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Is Associated With In-hospital Mortality in Older Patients With COVID-19

Abstract: Background The epidemic of COVID-19 presents a special threat to elderly adults. However, information on kidney damage in elderly patients with COVID-19 is limited. Acute kidney injury (AKI) is common in hospitalized adults and associated with a poor prognosis. We sought to explore the association between AKI and mortality in elderly patients with COVID-19. Methods We conducted a retrospective, observational cohort study in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
2
35
2
1
Order By: Relevance
“…Acute kidney injury, a common complication in hospitalized adults, is associated with poor prognosis. It has recently been related to higher mortality in patients ≥ 65 years old with COVID-19 ( 40 ), a finding that was also observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Acute kidney injury, a common complication in hospitalized adults, is associated with poor prognosis. It has recently been related to higher mortality in patients ≥ 65 years old with COVID-19 ( 40 ), a finding that was also observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, 11 studies (6, 9-18) with 8815 patients with COVID-19 ful lled eligibility criteria (Fig 1). Table 1 presents the summary characteristics of the 11 included studies [6,[9][10][11][12][13][14][15][16][17][18]. The prevalence of AKI ranged from 10.3% to 81%.…”
Section: Study Selectionmentioning
confidence: 99%
“…The prevalence of AKI ranged from 10.3% to 81%. Ten studies [6,[9][10][11][12][13][14][16][17][18] were single center, and one [15] was multicenter.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessing the full text, 176 were excluded because they did not report the association between IL-6 level and poor outcomes in COVID-19 patients, and 51 were excluded because original data were not reported or adjusted effect was not used. Finally, 16 articles consisting of 8752 COVID-19 patients were included in the meta-analysis (Ayanian et al 2020 ; Bellmann-Weiler et al 2020 ; Cummings et al 2020 ; Del Valle et al 2020 ; Li et al 2020 ; Liu et al 2020a , b , c , d , e ; Phipps et al 2020 ; Sardu et al 2020 ; Song et al 2020 ; Tian et al 2020 ; Wang et al 2020 ; Yan et al 2020 ). The characteristics of the 16 eligible studies are shown in Table 1 .…”
mentioning
confidence: 99%